The Effect of Work Family Conflict on Employee Performance with Job Satisfaction as a Mediating Variable at Rs Prima, Ternate City - Sajim, Nurlina; Marwan, Marwan; Sabuhari, Rahmat (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine the effect of work family conflict on performance mediated by job satisfaction. This research is a quantitative study with data collection techniques using a questionnaire. The sample in this study were permanent employees, totaling 74 employees. This research used a non-probability sampling technique using a purposive sampling method. The analytical tool used is path analysis with the help of the SPSS 29 program. The results showed that work family conflict has no significant effect on employee performance, work family conflict has a positive and significant effect on employee job satisfaction, job satisfaction has a positive and significant effect on employee performance, and job satisfaction are not able to mediate work family conflict on employee performance